2012
DOI: 10.1095/biolreprod.111.096610
|View full text |Cite
|
Sign up to set email alerts
|

Initiating Meiosis: The Case for Retinoic Acid1

Abstract: The requirement for vitamin A in reproduction and development was first determined from studies of nutritional deficiencies. Subsequent research has shown that embryonic development and both male and female reproduction are modulated by retinoic acid (RA), the active form of vitamin A. Because RA is active in multiple developmental systems, its synthesis, transport, and degradation are tightly regulated in different tissues. A growing body of evidence implicates RA as a requirement for the initiation of meiosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
120
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 54 publications
2
120
1
2
Order By: Relevance
“…To determine whether Rhox10 is regulated by differentiation cues in spermatogonial cells, we treated GS cells with retinoic acid (RA), a known inducer of germ cell meiosis (Bowles et al 2006, Anderson et al 2008, Griswold et al 2012. We found that RA treatment for 24 h dramatically increased Rhox10 mRNA level (Fig.…”
Section: Expression and Regulation Of Rhox10 In Gs Cellsmentioning
confidence: 95%
“…To determine whether Rhox10 is regulated by differentiation cues in spermatogonial cells, we treated GS cells with retinoic acid (RA), a known inducer of germ cell meiosis (Bowles et al 2006, Anderson et al 2008, Griswold et al 2012. We found that RA treatment for 24 h dramatically increased Rhox10 mRNA level (Fig.…”
Section: Expression and Regulation Of Rhox10 In Gs Cellsmentioning
confidence: 95%
“…This paradigm emerged from the ability of exogenous RA to induce premature meiotic initiation in fetal male GC (reviewed in ref. 5) and from VAD models, which display a meiotic failure simply because spermatogonia are blocked at the undifferentiated stage (e.g., ref. 35).…”
Section: Ra Is Necessary To Initiate Meiosis In Spermatocytes Througmentioning
confidence: 99%
“…In fact, vitamin A-deficient (VAD) mice are infertile because of an arrest of spermatogonia differentiation at the Aal-A1 transition, and treating them with either retinol or RA results in the complete recovery of spermatogenesis (3). As RA can trigger meiosis in female GC through initiating Stra8 expression (4,5) and can additionally induce Stra8 expression in male GC (3), the paradigm has become that RA is required for meiotic initiation. However, a recent study showing that female GC can enter meiosis in a fetal ovary devoid of RA has challenged this model (6).…”
mentioning
confidence: 99%
“…The importance of vitamin A in reproductive health in both males and females has been well documented (1,2). In males, either vitamin A deficiency (3) or mutations in genes involved in retinoid signaling pathways leads to perturbations in meiosis and spermatogenesis (1,2).…”
mentioning
confidence: 99%
“…In males, either vitamin A deficiency (3) or mutations in genes involved in retinoid signaling pathways leads to perturbations in meiosis and spermatogenesis (1,2). Because animals lack enzymes to synthesize vitamin A de novo, it has to be derived from dietary sources as preformed vitamin A from animal products and provitamin A carotenoids from fruits and vegetables (4).…”
mentioning
confidence: 99%